Analysis of Worker Productivity with Time Study Method on Column Work - Setiawati, Dwi Novi; Intari, Dwi Esti; Asyiah, Siti; Maddepunggeng, Andi; Ujianto, Rifky; Syahid, Mushab Abdu Asy; Damanik, Mariana Feronica; Dharmawan, Yoga (JURUSAN TEKNIK SIPIL, 2025)
This research discusses the value of worker productivity in building column work, there are several factors that affect the value of worker productivity, the value of productivity will affect various aspects of construction projects, including completion time, cost, and quality, therefore the organizers of construction projects must know the value of worker productivity when doing work. The research was conducted by conducting field observations to obtain column work time which was then analyzed using the Time Study method to determine the value of worker productivity and work costs. The results showed that the productivity value of Pamulang University column work was obtained in column reinforcement work of 544.07 kg/OH, in column formwork work of 42.01 m2/OH, in column casting work of 57.05 m3/OH, and in formwork dismantling work of 170.38 m2/OH. Factors that hinder productivity in Pamulang University column work, namely in column reinforcement work is the number of workers, in column formwork work is the number of workers and the position of workers, in column casting work is the number of workers, and in column formwork dismantling work is the position of workers and the number of workers. The cost required per column in the Pamulang University Development project is Rp6,727,870.00.